2021
DOI: 10.1007/s00251-021-01203-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the domestic goat γδ T cell receptor gene loci and gene usage

Abstract: Background Prognostic models to predict the risk of clinical deterioration in acute COVID-19 cases are urgently required to inform clinical management decisions. Methods We developed and validated a multivariable logistic regression model for in-hospital clinical deterioration (defined as any requirement of ventilatory support or critical care, or death) among consecutively hospitalised adults with highly suspected or confirmed COVID-19 who were prospectively recruited to the International Severe Acute Respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Its preservation for such a long evolutionary time, implies a highly specialized function of its genes, which could be essential for the survival of the species. For instance, it has been shown that the genes within the TRGC5 cassette would preferentially be expressed in specific γδ cell populations in pigs as well as in ruminants [ 39 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its preservation for such a long evolutionary time, implies a highly specialized function of its genes, which could be essential for the survival of the species. For instance, it has been shown that the genes within the TRGC5 cassette would preferentially be expressed in specific γδ cell populations in pigs as well as in ruminants [ 39 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its preservation for such a long evolutionary time, implies a highly specialized function of its genes, which could be essential for the survival of the species. For instance, it has been shown that the genes within the TRGC5 cassette would preferentially be expressed in specific gd cell populations in pigs as well as in ruminants [39,45].…”
Section: Discussionmentioning
confidence: 99%
“…43 Conversely, αβ T cells become prevalent in the thymus around 10 PCW, while the first naive αβ T cells egress the gland and migrate toward the periphery around 11 or 12 PCW. 43 Even-toed ungulates (Artiodactyla), which include several TCR γδ high (γδ-hi) species such as pig and goat, 30,45,46 appear to follow an "early" pattern of γδ thymocyte wave like in human (Figure 1), achieving adult-like levels of γδ thymocytes and a diverse TCR repertoire before birth. [46][47][48] Intriguingly, even though γδ-hi species possess high levels of γδ T cells in the periphery during mid-late gestation and the first year of life, the proportion of γδ thymocytes remains relatively low than their conventional αβ counterparts 30,49 (Figure 1).…”
Section: γδ T Cell Ontog Eny the Fir S T T Cell Wave Across E Voluti Onmentioning
confidence: 99%